2019
DOI: 10.1128/mcb.00063-19
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Broadly Regulates the Initiation of Skeletal Muscle-Specific Gene Expression by Binding Target Promoters and Facilitating the Interaction of the SWI/SNF Chromatin Remodeling Enzyme

Abstract: Calcineurin (Cn) is a calcium-activated serine/threonine protein phosphatase that is broadly implicated in diverse cellular processes, including the regulation of gene expression. During skeletal muscle differentiation, Cn activates the nuclear factor of activated T-cell (NFAT) transcription factor but also promotes differentiation by counteracting the negative influences of protein kinase C beta (PKCβ) via dephosphorylation and activation of Brg1, an enzymatic subunit of the mammalian SWI/SNF ATP-dependent ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 95 publications
0
20
2
Order By: Relevance
“…Chromatin immunoprecipitation assays were performed as described previously ( 73 ). Quantification was performed using the fold enrichment method (2 –(Ct sample – Ct IgG) ) and shown as relative to a control region.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatin immunoprecipitation assays were performed as described previously ( 73 ). Quantification was performed using the fold enrichment method (2 –(Ct sample – Ct IgG) ) and shown as relative to a control region.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro work identified serine residues N-and C-terminal to the bromodomain of BRG1 as targets of PKCβ 1 and calcineurin [49]. Site directed mutagenesis studies demonstrated that mutation of these sites to phosphomimetic residues prevented myogenesis because the phosphomimetic BRG1 mutant was unable to bind to myogenic promoters while mutation of PKCβ 1 target sites to non-phosphorylatable (alanine) residues had no effect on chromatin binding or differentiation [49,188]. Calcineurin inhibition also blocked the interaction of other subunits of the mSWI/SNF complex with myogenic promoters [188].…”
Section: The Pkcβ 1 Kinase and The Calcineurin (Cn) Phosphatase Act Imentioning
confidence: 99%
“…Site directed mutagenesis studies demonstrated that mutation of these sites to phosphomimetic residues prevented myogenesis because the phosphomimetic BRG1 mutant was unable to bind to myogenic promoters while mutation of PKCβ 1 target sites to non-phosphorylatable (alanine) residues had no effect on chromatin binding or differentiation [49,188]. Calcineurin inhibition also blocked the interaction of other subunits of the mSWI/SNF complex with myogenic promoters [188]. This raises the possibility of regulated dephosphorylation of other mSWI/SNF subunits or an indirect effect due to the failure to dephosphorylate BRG1.…”
Section: The Pkcβ 1 Kinase and The Calcineurin (Cn) Phosphatase Act Imentioning
confidence: 99%
“…We and others have shown that the activity of Brg1 and other components of the mSWI/SNF complex is post-translationally regulated by various signaling pathways [16][17][18][19][20][21][22]. For instance, in the liver, BAF60c phosphorylation via the insulin-signaling pathway enables the expression of lipogenic genes [23].…”
Section: Introductionmentioning
confidence: 99%
“…mSWI/SNF enzymes are required for myoblast proliferation and at multiple stages of differentiation [27][28][29][30][31][32]. Regulated phosphorylation and dephosphorylation of Brg1 is an essential part of both proliferation and differentiation [16,17,22]. Phosphorylation of Brg1 by protein kinase C β1 (PKCβ1) prior to the induction of differentiation signaling has a repressive effect on the function of Brg1 and leads to a block of myogenic differentiation [16].…”
Section: Introductionmentioning
confidence: 99%